GEODYNAMIC CONDITIONS OF VOLCANISM AND MAGMA FORMATION IN THE KURILE-KAMCHATKA ISLAND-ARC SYSTEM - Avdeiko G.P.; Palueva A.A.; Khleborodova O.A. (My University, 2006)
The conditions of magma formation were reconstructed on the basis of characteristic features of the evolution of the Kurile-Kamchatka island-arc system, structural and chemical zoning patterns of volcanic complexes, and available published data on peridotite and basalt melting and stability of hydrous minerals. It was shown that the volcanic arc of the Sredinnyi Range of Kamchatka occurs now at the final stage of subduction, whereas subduction beneath the volcanic arc of eastern Kamchatka began at the end of the Miocene, after its jump into the present-day position. The volcanism of Southern Kamchatka and the Kuriles has occurred under steady-state subduction conditions since the Miocene and is represented by typical island-arc magmas. The latter are generated in a mantle wedge, where the melting of water-saturated peridotite occurs in a high-temperature zone under the influence of fluid. The formation of the frontal and rear volcanic zones was related to the existence of two levels of water release from various hydrous minerals. During the initial and final stages of subduction, as well as in the zone of Kamchatka—Aleutian junction, partial melting is possible in the upper part of the subducted slab in contact with a hotter mantle material compared with the mantle in a steady-state regime. This is responsible for the coexistence of predominant typical island-arc rocks, rocks with intraplate geochemical signatures, and highly magnesian rocks, including adakites.